Co-culture Activation of MAP Kinase in Drosophila S2 Cells - Steinhauer, Josefa (Methods Mol Biol, 2017)
Intercellular communication often involves phosphorylation of signal transduction proteins, including mitogen-activated protein kinases (MAPKs). Immunological detection of phosphorylated MAPK can be used to monitor signaling in vivo, identify novel pathway components, and assess ligand activity. In this chapter, I describe a cell co-culture method to assess activity of cell-bound extracellular ligands that result in phosphorylation of the ERK (extracellular signal-regulated kinase) MAPK in Drosophila. This protocol may be adaptable to other pathways and/or model systems.